Unveiling the Symbolic Meaning and Function of Tu Dhe'u Ritual: A Semiotic Analysis of Rodent Control Practice in Maluriwu Village - Maria Kartini; Yoanita Dewi Roswita Kolo (Dinasti Publisher, 2025)
This research explores the symbolic meanings and functions of the Tu Dhe’u ritual, an agricultural ceremony performed by the Maluriwu community in response to rat infestations. This research aimed to unveil the symbolic meanings and function of the Tu Dhe’u ritual using Roland Barthes's semiotic approach. To collect the data, the researchers conducted an unstructured interview to explore the informants’ perspectives on the Tu Dhe’u ritual’s symbolic meaning and function. The data were subjected to qualitative analysis using a descriptive approach. The findings indicated several symbolic elements embedded within each stage of the Tu Dhe’u ritual such as Dhe’u (rats), Sope (rat boat), Pa’e (prayers), Purification using coconut water, Traditional Sites, Sea, Tua Ka, Tu Laja, and Phije.